Customer loyalty: The case of mobile phone users in Universiti Utara Malaysia - Achour, Meguellati; Md Said, Nor Pujawati; Boerhannoeddin, Ali (Universiti Utara Malaysia, 2011)
This research attempts to examine the relationships between service quality, switching barriers and brand image and customer loyalty in the Universiti Utara Malaysia sector. Based on the theoretical model, a comprehensive set of hypotheses were formulated and a methodology for testing them was outlined.These hypotheses were tested empirically by means of questionnaires to demonstrate the applicability of the theoretical model.The results indicate that service quality, switching barriers, and brand image are separate constructs that combine to determine loyalty, with service quality and switching barriers exerting a stronger influence than brand image.Hypotheses H1, H2 were supported, while hypothesis H3 was rejected.